Analyzing Fcγ-Receptor Interactions on Monocytes with the Proximity Ligation Assay (PLA) - Kara, Sibel; Nimmerjahn, Falk (Methods in Molecular Biology, 2024)
Proximity ligation assays (PLA) enable the detection and characterization of protein interactions independent of protein abundance or genetic modifications. This technique exploits both antibody and DNA-binding features, providing high selectivity and sensitivity for protein recognition and visualization of single-protein molecules with high spatial accuracy. Here, we describe the general procedure for a direct PLA on splenic monocytes to analyze FcγRIIb homodimerization. However, this method can be applied to other cells and receptors of interest.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Antibody; Fc receptor; Microscopy; Protein interaction; Proximity ligation assay (PLA)